How Experts Understand the Public in Vaccination Controversies in Chile [Cómo Los Expertos Entienden Al Público en Las Controversias Sobre Vacunación en Chile] - Broitman-Rojas, C; Jara-Reyes, R; Rocamora-Villena, V (CSIC Consejo Superior de Investigaciones Cientificas, 2019)
The socio-scientific controversies regarding vaccination that have emerged in Chile in recent years have exposed new tensions between experts and citizens. Numerous research studies about these controversies have focused on analyzing the viewpoints of citizens who oppose vaccination, but have overlooked other relevant actors, such as the experts. Based on a qualitative approach, this article analyzes the discourse, strategies and communication practices of health experts, in order to understand their standpoint in relation to citizens who oppose vaccination. The research shows that in spite of unanimous agreement about the relevance of vaccination as a preventive policy, expert positions about these citizens differ. This is reflected in different Public Communication of Science and Technology models, with a clear prevalence of the deficit model. © 2019 CSIC.